New Entropy-Based Similarity Measure between Interval-Valued Intuitionstic Fuzzy Sets - Saida S. Mohamed; Areeg Abdalla; Robert I. John (Axioms, 2019)
In this paper, we propose a new approach to constructing similarity measures using the entropy measure for Interval-Valued Intuitionistic Fuzzy Sets. In addition, we provide several illustrative examples to demonstrate the practicality and effectiveness of the proposed formula. Finally, we use the new proposed similarity measure to develop a new approach for solving problems of pattern recognition and multi-criteria fuzzy decision-making.